Graphene-Based Integrated Photovoltaic Energy Harvesting/Storage Device - Chien, Chih-Tao; Hiralal, Pritesh; Wang, Di-Yan; Huang, I-Sheng; Chen, Chia-Chun; Chen, Chun-Wei; Amaratunga, Gehan A. J. (Small (Weinheim an der Bergstrasse, Germany), 2015)
Energy scavenging has become a fundamental part of ubiquitous sensor networks. Of all the scavenging technologies, solar has the highest power density available. However, the energy source is erratic. Integrating energy conversion and storage devices is a viable route to obtain self‐powered electronic systems which have long‐term maintenance‐free operation. In this work, we demonstrate an integrated‐power‐sheet, consisting of a string of series connected organic photovoltaic cells (OPCs) and graphene supercapacitors on a single substrate, using graphene as a common platform. This results in lighter and more flexible power packs. Graphene is used in different forms and qualities for different functions. Chemical vapor deposition grown high quality graphene is used as a transparent conductor, while solution exfoliated graphene pastes are used as supercapacitor electrodes. Solution‐based coating techniques are used to deposit the separate components onto a single substrate, making the process compatible with roll‐to‐roll manufacture. Eight series connected OPCs based on poly(3‐hexylthiophene)(P3HT):phenyl‐C61‐butyric acid methyl ester (PC60BM) bulk‐heterojunction cells with aluminum electrodes, resulting in a ≈5 V open‐circuit voltage, provide the energy harvesting capability. Supercapacitors based on graphene ink with ≈2.5 mF cm−2 capacitance provide the energy storage capability. The integrated‐power‐sheet with photovoltaic (PV) energy harvesting and storage functions had a mass of 0.35 g plus the substrate. Simultaneous energy harvesting (organic photovoltaic cell) and energy storing (supercapacitor) functionalities are integrated onto a single substrate by using graphene in different forms and qualities. Organic photovoltaic cells provide ≈5 V open‐circuit output to charge the supercapacitor (≈2.5 mF cm−2 capacitance), results in a self‐powered system used to drive RGB light emitting diode.